Influence of particle size and dielectric environment on radiative lifetimes of colloidal cadmium selenide single photon emitters - V. Manojkumar; Geetha K. Varier; Radhika Vathsan; P. Nandakumar (Scientific Reports)
Abstract High repetition rate single-photon emitters are essential for all-optical quantum information processing, communications and metrology. The spontaneous emission lifetimes of colloidal cadmium selenide quantum dots are typically of the order of 10 ns, severely limiting their brightness and therefore their potential applications in quantum devices. Here we report on single-photon emission at room temperature with nanosecond lifetime from cadmium selenide quantum dots embedded in a polymer matrix. The study shows that the emission lifetime can be tuned by appropriately choosing the particle size and the dielectric constant of the surrounding medium. The quantum dots are synthesized using a green synthesis protocol and surface passivated using oleic acid. A Hanbury Brown and Twiss setup attached to an in-house constructed confocal microscope is used to efficiently couple and characterize the single-photon emission from an array of quantum dots. Detailed analysis of the second-order correlation function ( $$g^{(2)}(τ )$$ ) of single-photon emission from cadmium selenide quantum dots reveals the particle-size dependence of emission lifetimes. The study also shows that the quality of single-photon emission, as revealed by $$g^{(2)}(0)$$ , reduces with increasing particle-size in the strongly confined regime.